The application of restorative justice as a settlement of domestic syiqaq in QS. An-Nisa verses 34 and 34 according to the view of wahbah az-zuhaili in the book of tafsir al-munir - Hisan, Khairatun; Zuhri, Ahmad; Simamora, Nur Aisah; Harahap, Mardian Idris (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
In this research the focus is on how is shiqaq resolved? Then in this research we also discuss how in the household if there is syiqaq then there must be steps taken to resolve it, and in this research the researcher wants to examine how restorative justice is implemented regarding syiqaq in the household, and the researcher also examines how to implement restorative justice syiqaq in this household in Qs. An-nisa verse 34 in the thoughts of Wahbah Az-Zuhaili. The method used in this research is a qualitative method. This type of research is library research, meaning that this research focuses on literature by analyzing the content of the literature related to the research. The data collected in this research is by looking for cases of syiqaq in society and then collecting them as reinforcement in the research, then the researcher examines the implementation of restorative justice by taking examples from the community and comparing them with Islamic laws to see whether they are in line with or not. no, after that the researcher took the interpretation of Wahbah Azzuhaili in Qs. An-nisa verse 34 which relates to research. After all the data has been collected, the researcher begins the research. The sources for this research are books, journals, theses, articles discussing restorative justice, syiqaq and referring to Al-munir's interpretation. The conclusion of the research is that Wahbah Az-Zuhaili's view is that in the family it is the man who has the duty to educate his wife to be better, but in this case there are several types of wives, namely wives who obey their husbands, and there are wives who are obedient to their husbands. who disobeys her husband. If the wife disobeys her husband then the husband can advise, scold, separate the bed and even the husband can hit his wife on condition that it does not leave scars, wounds and bruises on her body, and if that happens then the wife can ask for protection from the family or even the court but as far as possible to maintain the marriage because Allah does not recommend divorce. In this research, the contribution of this research is to clarify whether this application is in line with the Islamic view which is strengthened by Az-Zuhaili's Thought.